Lippincott nursing procedures. (Philadelphia : Wolters Kluwer, 2015)
Resource added for the Nursing-Associate Degree 105431, Practical Nursing 315431, and Nursing Assistant 305431 programs.
Preceded by Lippincott's nursing procedures. 6th ed. c2013.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nursing; Nursing Care; Evidence-Based Nursing; Electronic books